Development of Numbers Material Test Using the Item Response Theory (IRT) Approach for SD Students - Ahmad Rustam; Kasmawati Kasmawati (USN Kolaka, 2021)
The purpose of the research is to produce a product in the form of a valid and reliable measuring instrument for student numeracy that can be used in schools and in the general public. The research stages will be carried out based on the test development design, namely Preparing Test Specifications, Preparing Test Items, Testing Test Items in the Field, Revision of Test Items, and Test Development. The question grid is based on the 2013 curriculum syllabus. The test was conducted on elementary school students. The response of the test results in the form of dichotomous data and analyzed using the item response theory (IRT) model with two logistical parameters (2PL), namely the level of item difficulty and item discriminating power. Estimation of item parameters and capability parameters using the BILOG MG program. Before doing item analysis with IRT. The results of the study contained 18 items that could be used to measure students' numeracy skills. Among these items are numbered questions 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, and 18. meet the criteria of a good item including having a good difficulty level, then the distinguishing power of the item functions well and has good validity and reliability.